Madagascar - Poverty and Socioeconomic Developments : 1993 - 1999 - World Bank (Washington, DC, 2013)
The report provides a synthesis of the main results obtained on the evolution of poverty, and other indicators of well being over the 1990s, and is intended to facilitate debate on strategy options for poverty reduction in Madagascar. Section I provides the setting for study, and presents a synthesis of macroeconomic trends in the country during the last decade. Section II looks at the evolution of poverty, inequality, and other indicators over the 1993-1999 period. The analysis is developed both at the national, and regional level, and, when possible, international comparisons are presented. Section III further investigates which groups have been more vulnerable to economic changes during the 1990s, and which factors can help explain this evolution over time. Section IV examines developments in provision of health, and education services by reviewing the degree of program coverage, and progressiveness of services in the two sectors. Section V presents community perceptions of socioeconomic development priorities, namely physical infrastructure development, while Section VI examines the prospects for poverty reduction of different growth rates of the economy as a whole for the next twenty years, and by further investigating the potential impact of different sectoral patterns of growth. Further work should be focused on understanding the causes for geographic variations in poverty, and on the functioning of agricultural labor and land markets, to include a labor market analysis focused on off-farm employment, as a route out of poverty. Most importantly, a thorough understanding of the poverty impact of recent reforms is recommended, to build successful anti-poverty policies.